Peningkatan Teknik Pounding Terinspirasi Happa-Zome dalam Kegiatan Pembuatan Tekstil Ramah Lingkungan di PPSA “Taruna Yodha” Sukoharjo - Tiwi Bina Affanti Bina Affanti; Ratna Endah Santoso; Sarwono Sarwono; Adji Isworo Josef; Lira Anindita Utami (Abdi Seni, 2023)
This community service is carried out with the participation of PPSA (orphanage) Taruna Yodha in Sukoharjo, Central Java. By creating textile products, the activity that incorporates an eco-friendly production process inspired by the Japanese Happa-zome technique (manual leaf-printing decoration technique) is chosen and improved to motivate environmental awareness while strengthening the entrepreneurial capacity of the beneficiaries. The service program is conducted by (in)direct presentation and mentoring, a participatory and iterative process from the beginning to the end. Within the program, design survey activity in the form of exploring nature's potential involves introducing the surrounding natural environment while collecting leaf material. The results are; (1) Providing environmental awareness for beneficiaries through textile-making, (2) the Happa-zome technique for interior textile product development, (3) creating an Entrepreneurial program including story-making and online marketing strategy